Rapidly making biodegradable and recyclable paper plastic based on microwave radiation driven dynamic carbamate chemistry - Xinxin Yang; Le Yu; Bowen Zhang; Yongheng Wang; Xiangzheng Jia; Erlantz Lizundia; Chang Chen; Fuhao Dong; Luhe Qi; Lu Chen; Enlai Gao; Xu Xu; et al. (Nature Communications)
Abstract In response to the looming concerns of plastic pollution, replacing plastic with paper is a very promising way, but its realization seems a long way off due to the poor water resistance and unsatisfied mechanical strength of cellulose fibril-based materials. Herein, we develop a versatile functionalizing material consisting of mainly biobased cyclic carbonate-bearing compounds and amine compound, which can enable the rapid transformation (within 2 min under microwave radiation) of the cellulose paper into plastic-like material (named paper plastic) having an unprecedently high tensile strength of ~126 MPa. Through a systematic experimental and theoretical study, the paper plastic’s combination of excellent mechanical properties and water/solvent resistance is attributed to the easy formation of carbamate abundant non-isocyanate polyurethane cooperated with the intermolecular bond exchange mechanism between the dynamic carbamate moiety and hydroxyl of the cellulose. Also, benefiting from the high content (>80%) and natural advantages of biobased materials, the paper plastic shows significant thermal stability, processability, and biodegradability than most petrochemical-based plastics, promising the great potential of dynamic carbamate chemistry toward high-performing paper plastic composites.